SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN SEKOLAH MENENGAH KEJURUAN (SMK) UNGGULAN DI WILAYAH LAMPUNG TENGAH MENGGUNAKAN METODE TOPSIS - Febri Ariyanto; Muhamad Muslihudin (Jurnal TAM (Technology Acceptance Model), 2015)
Determining Appropriate And Best school is not easy. We Must Finding information in schools Yang kita go, then compare and choose which school Suitable Match Criteria. as well as determine the SMK in the region of Central Lampung We Must determine Of different aspect as Material Considerations for review determine SMK seed, and therefore we use a system of decision support using methods Techniques for Preference Order by Similarity to Ideal Solution (TOPSIS) as a method of deciding SMK Featured , Decision Support System (DSS) is a Computer Based Interactive Systems Able to help the local decision makers hearts using data and models to solve an issue reviews are not structured. SPK with Method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is used for the reviews completed a structured issue Operate Its not simple. Verifying with checklists so that the method, can be doing Effective Decision Making Process. At about articles Singer will discuss the modeling application Method Method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) hearts determine school SMK (vocational) seed. Criterion Criterion hearts Decisions Needed That Facilites C1, C2 C3 Accreditation Quality, HR Student C4, C5 Costs.